Silk fibroin fiber skeleton reinforced composite gel ball as well as preparation method and application thereof
By preparing silk fibroin fiber skeleton-reinforced composite gel balls, the problem of insufficient structure and performance of materials in tissue regeneration applications in the existing technology is solved, and the mechanical properties, injectability and structural stability of the material are achieved, making it suitable for soft tissue Augmentation and local tissue regeneration treatments.
Patent Information
- Application Number
- CN202411931620.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, sodium hyaluronate and silk fibroin materials have problems with insufficient structure and performance in tissue regeneration applications, including weak cell affinity, insufficient cohesion, large rigidity, insufficient flexibility, difficulty in injection, and degradation rate. Wait too soon.
Enhance the composite gel balls by preparing syringin protein fiber skeleton, and use unchanging or modified sodium sodium hyaluronic acid sodium and chemical cross -hyaluronic acid sodium to form a composite gel ball to enhance the micronicular fiber Interaction between the intercourse and form gel microspheres through chemical cross -linking to achieve the mechanical properties, injections and structural stability of the material.
The mechanical properties of the material are controllable, both rigid and flexible, the internal agglomeration is large, can withstand the shear effect and maintain structural stability. At the same time, it has good cell compatibility and biocompatibility. It is suitable for soft tissue filling and local tissue regeneration treatment.
Smart Images

Figure CN119345480A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and in particular to a silk fibroin fiber skeleton reinforced composite gel ball and a preparation method and application thereof. Background Art
[0002] The loss of local tissues caused by chronic diseases, accidental injuries, trauma, aging, etc. due to aging is a major problem that needs to be solved in the medical field. It often requires replacement or transplantation of regenerative tissues. Autologous transplantation or allogeneic transplantation faces a huge risk of immune tissue rejection, and the cost is high and the patient's tolerance is low.
[0003] The extracellular matrix is an important component of human tissues and organs. It can provide structural and physical support for cells, and can also have a profound impact on various physiological activities of cells through signal transduction systems. It is becoming increasingly possible to repair damaged or replenish lost tissues through tissue engineering technology. Using biomaterials to simulate the extracellular matrix to load cells and promote cell adhesion and proliferation is the key to tissue regeneration. Polysaccharides and proteins are the main components of the extracellular matrix, and they play an important role in supporting the morphology of the extracellular matrix, regulating cell growth and normal physiological activities. At present, the research on biomaterials that simulate the extracellular matrix is mostly based on two natural polymer materials, sodium hyaluronate and collagen. However, there are problems. On the one hand, the cross-linked sodium hyaluronate gel has a repulsive effect of a highly hydrated layer on its surface, and its cell affinity is weak, making it difficult for cells to migrate, adhere, proliferate, differentiate, and regenerate and repair defective soft tissues in the extracellular matrix of sodium hyaluronate gel; on the other hand, the cross-linked sodium hyaluronate has insufficient cohesion and is prone to "bun" during tissue filling; the biomaterials prepared from collagen have insufficient mechanical strength and uncontrollable degradation rate, especially when the triple helix structure is unraveled, the fragile areas in the collagen are exposed, and are easily rapidly degraded into amino acids by many proteases. In addition, when used as cell carrier materials, both sodium hyaluronate and collagen have short in vivo mechanical half-lives and too fast degradation rates, and cannot effectively promote tissue regeneration.
[0004] Silk fibroin extracted from silk is a fibrous protein composed of 18 kinds of human amino acids. Silk fibroin has low immunogenicity and excellent plasticity. The prepared gel, scaffold and nano-micron fiber biomaterials have strong mechanical properties. In addition, the degradation rate when implanted in the body is significantly slower than that of materials such as sodium hyaluronate, collagen and gelatin. It has good adhesion and guided migration ability to most human cells, can guide soft tissue regeneration and repair, can simulate the protein components and functions in human tissues, and the degradation products are non-toxic, highly safe, and have excellent biocompatibility. It is one of the most promising new biomedical materials.
[0005] However, there are still many limitations in the existing technology. There are a large number of hydrophobic amino acids in the macromolecular chain segments of silk protein, and the hydrophilic and water-retaining properties of the formed gel are poor; high-crystallinity silk protein gel will have volume shrinkage and hardening behavior, which is easy to cause increased brittleness and insufficient flexibility; silk protein scaffold scaffold materials are relatively rigid and have poor injectability, and often require open implantation, which causes large surgical trauma, increases surgical risks and increases patient pain. Therefore, pure silk protein materials can no longer meet the needs of tissue regeneration. In recent years, composite materials that simulate extracellular matrix have been developed for soft tissue regeneration and repair. For example, silk protein micron particles are used as basic structural units, and free hyaluronic acid is used as a filler for lubricating suspension medium. It has been applied to vocal cord injury repair, cartilage repair and regeneration and other tissue regeneration fields. The silk protein micron particles lack sufficient mutual attraction, and it is difficult to maintain the structural stability of the material after injection of high shear, and it is impossible to achieve the recovery of mechanical strength, and the injectability is poor. Compared with nano-micron particles, the interaction force between nano-micron fibers is stronger (entanglement, cohesion), and the structural stability can be better maintained when subjected to high shear force. Patent CN 108553689 A discloses porous microspheres prepared with nanofibers as the matrix, which need to be treated with alcohol to improve their mechanical properties. They are very rigid and lack flexibility, making them difficult to inject through needles above 27G. In addition, the preparation conditions are harsh (-30℃--50℃).
[0006] In view of the above limitations, the preparation of reinforced composite gel based on two polymer materials, silk fibroin / sodium hyaluronate, which can mimic the extracellular matrix to the greatest extent, has high viscoelasticity and cohesion, injectability and maintains structural stability, and the coordination of degradation rate and tissue regeneration rate is the development direction of future product development to achieve its use as a tissue regeneration or even bionic repair and filling preparation. However, up to now, there has been no report on products and related inventions based on silk fibroin nano-micron fibers as reinforcing materials for constructing silk fibroin / sodium hyaluronate composite gel spheres. The reason is that silk fibroin macromolecules and sodium hyaluronate macromolecules have obvious differences in physical and chemical properties. For example, different hydrophilicity and electrostatic interactions will show different solubility. Furthermore, if silk fibroin and sodium hyaluronate are introduced into the same dissolution system, the two macromolecules will show strong interaction, weak attraction or weak repulsion under the combined action of covalent bonds, electrostatic forces, hydrogen bonds, van der Waals forces, hydrophobic effects, ionic bonds, volume exclusion effects and molecular chain curling between different fragments and side chains on their respective molecular chains: 1) flocculation and precipitation together; 2) metastable slightly soluble complexes; 3) maintaining a uniform and stable dissolution state (uniform mixing is required under conditions where the pH is higher than the isoelectric point of the protein). In fact, in the process of forming silk fibroin nano-micron fibers, the existence of surface / interface effects at the microscopic scale makes it more difficult to maintain a thermodynamic equilibrium state (neither strongly repelling nor strongly attracting) between the silk fibroin / sodium hyaluronate phases, and the existing technology usually requires the introduction of additional components such as polar / non-polar organic reagents, surfactants, electrolytes and cross-linking agents into the two-phase dissolution system, which brings new factors affecting the equilibrium stability of macromolecules in the nanodomain, making it extremely difficult to achieve uniform and stable composite of silk fibroin / sodium hyaluronate phases at the nanoscale, which also makes it a difficult problem to manufacture the silk fibroin / sodium hyaluronate composite nanofibers composed of bionic organisms and form reinforced composite gel balls on this basis.
[0007] The present invention aims at the problems existing in the application of biological materials such as sodium hyaluronate, collagen and silk fibroin in tissue regeneration, combines the water retention and lubricity of sodium hyaluronate with the excellent mechanical properties, slow degradation and cell adhesion of silk fibroin, and provides a silk fibroin fiber skeleton reinforced composite gel ball and its preparation method and application. Summary of the invention
[0008] Based on this, the purpose of the present invention is to provide a silk protein fiber skeleton reinforced composite gel ball and its preparation method and application, so as to solve the structural and performance deficiencies of the current single sodium hyaluronate and silk protein materials, including the repulsive effect of the highly hydrated layer on the surface of the sodium hyaluronate gel, its weak cell affinity, and it is difficult for cells to migrate, adhere, proliferate, differentiate and regenerate and repair defective soft tissue in the sodium hyaluronate gel as the extracellular matrix; the cross-linked sodium hyaluronate has insufficient cohesion and is easy to "bun" during tissue filling; the silk protein gel has small pores, which is not conducive to cell adhesion and proliferation; the high crystallinity silk protein gel will shrink and harden, which is easy to cause increased brittleness and insufficient flexibility; the silk protein scaffold has poor hydrophilicity and high rigidity and is difficult to directly Injection; The preparation conditions of silk fibroin nanofiber porous microspheres are harsh, and there are also technical problems such as high brittleness caused by high crystallinity and poor structural integrity of the material after injection and shearing. The prepared silk fibroin fiber skeleton reinforced composite gel spheres can make up for the shortcomings of a single material and have the following advantages: (1) controllable mechanical properties, both rigidity and flexibility, strong cohesion, and the ability to withstand shear forces while maintaining the structural stability of the material itself; (2) nano-micron fiber microstructure, simulating the structure and morphology of the extracellular matrix, which is conducive to cell adhesion and proliferation; (3) injectable, with small wounds during use, simple operation, and less pain for patients; (4) controllable degradability, and the tissue regeneration rate is coordinated with the material degradation rate in vivo, which is conducive to tissue repair and regeneration.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] According to the first aspect of the present invention, a silk fibroin fiber skeleton reinforced composite gel ball is provided, wherein the silk fibroin fiber skeleton reinforced composite gel ball consists of two parts: a skeleton material and a matrix material, wherein the skeleton material consists of unmodified or modified silk fibroin nano-micron fibers, and the matrix material consists of chemically cross-linked unmodified or modified sodium hyaluronate, and the average particle size range of the silk fibroin fiber skeleton reinforced composite gel ball is 10 μm to 10 mm, the content of the silk fibroin nano-micron fibers in the silk fibroin fiber skeleton reinforced composite gel ball is greater than the content of the sodium hyaluronate, and the diameter of the silk fibroin nano-micron fibers in the skeleton material is 10 nm to 30 μm.
[0011] Furthermore, the silk fibroin fiber skeleton reinforced composite gel sphere involved in the present invention is composed of two parts: a skeleton material and a matrix material. The chemically cross-linked sodium hyaluronate plays a "welding" role on the silk fibroin nano-micron fibers, thereby enhancing the interaction between the silk fibroin nano-fibers and "welding" the silk fibroin nano-micron fibers into a spherical gel.
[0012] As an implementation method, the silk fibroin nano-micron fiber is composed of unmodified silk fibroin or modified silk fibroin, and the modified silk fibroin is obtained by modifying the unmodified silk fibroin with a first type of functional group, and the first type of functional group includes one or more of alkyl, amino, carboxyl, sulfonic acid, thiol, epoxy, azo, imidazole, pyrimidine, maleimide, biotin, bindin, and fluorescent groups, and the molecular weight of the unmodified or modified silk fibroin ranges from 1 to 500 kDa; the modified sodium hyaluronate is obtained by modifying the unmodified sodium hyaluronate with a second type of functional group, and the second type of functional group includes one or more of alkyl, acyl, amino, aldehyde, cyano, hydrazide, thiol, imidazole, pyrimidine, biotin, bindin, and fluorescent groups.
[0013] As an implementation method, the modified silk fibroin is a covalently cross-linked silk fibroin obtained by reacting a compound with hydroxyl groups and amino groups in the silk fibroin molecules, and the modified sodium hyaluronate is a covalently cross-linked modified sodium hyaluronate obtained by reacting a compound with hydroxyl groups in the sodium hyaluronate molecular chain, and the compound is one or more of acrylic anhydride, acryloyl chloride, methacrylic anhydride, methacryloyl chloride, ethylacrylic anhydride, ethylacryloyl chloride, hydroxyacrylic anhydride, and hydroxyacryloyl chloride.
[0014] As an implementation method, the crosslinking agent for chemical crosslinking is one or more of 1,4-butanediol diglycidyl ether, diglycidyl ether, 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether, bisphenol A diglycidyl ether derivatives, resorcinol diglycidyl ether, 3,4-hydroxyphenylmethane triglycidyl ether and neopentyl glycol diglycidyl ether; preferably, the crosslinking agent is 1,4-butanediol diglycidyl ether.
[0015] As an implementation method, the average particle size of the silk fibroin fiber skeleton reinforced composite gel sphere is in the range of 100 μm to 500 μm, and the diameter of the silk fibroin nano-micron fiber in the skeleton material is in the range of 100 nm to 10 μm.
[0016] According to the second aspect of the present invention, there is provided a method for preparing a composite gel ball reinforced with a silk fibroin fiber skeleton, comprising: step S1: mixing an unmodified or modified silk fibroin solution with a denaturation inducer solution having a physical cross-linking effect, promoting physical cross-linking between silk fibroin molecules through hydrogen bonds and hydrophobic effects through external stimulation to form unmodified or modified silk fibroin nanometer micrometer fibers, and obtaining an unmodified or modified silk fibroin nanometer micrometer fiber suspension after washing and centrifugation; wherein the external stimulation comprises one or more of shear force, salt ions, temperature, pressure, and electric field force; step S2: dispersing the obtained unmodified or modified silk fibroin nanometer micrometer fiber suspension in a non-polar solvent to form a blended solution, and then adding an unmodified or modified sodium hyaluronate solution to the blended solution, stirring evenly, and then adding a cross-linking agent to carry out a cross-linking reaction to obtain a suspension of composite gel balls reinforced with a silk fibroin fiber skeleton; step S3: adding a cleaning agent to the suspension of composite gel balls reinforced with a silk fibroin fiber skeleton, and obtaining composite gel balls reinforced with a silk fibroin fiber skeleton after washing and centrifugation.
[0017] As an implementation method, the denaturation inducing agent solution that acts as a physical cross-linking agent is one or more of methanol, ethanol, isopropanol, acetone, 2-phenylethanol, phenoxyethanol, and polyethylene glycol. If the unmodified or modified silk fibroin solution is mixed with the polyethylene glycol solution, stirred at 2500 rpm for 30 seconds, and washed and centrifuged to obtain silk fibroin nano-micron fibers with relatively uniform thickness and length, then step S1 is performed.
[0018] As an implementable embodiment, the molecular weight range of polyethylene glycol in the polyethylene glycol solution is 200-20000Da, and the mass volume concentration of the polyethylene glycol solution is 50-100w / v%; preferably, the molecular weight range of polyethylene glycol in the polyethylene glycol solution is 200-400Da, and the mass volume concentration of the polyethylene glycol solution is 70-90w / v%.
[0019] As an implementable embodiment, the mass volume concentration of the unmodified or modified silk fibroin solution is 5 to 40 w / v%; preferably, the mass volume concentration of the unmodified or modified silk fibroin solution is 15 to 25 w / v%.
[0020] As an implementable embodiment, in step S2, the unmodified or modified sodium hyaluronate solution is compounded using an alkaline solution, first preparing a 0.01-2% sodium hydroxide solution with a pH of 8-13; preferably, preparing a 1% sodium hydroxide solution, and the pH of the blended solution in step S2 is 9.5.
[0021] As an implementation method, the mass volume concentration of the unmodified or modified sodium hyaluronate solution is 0.1 to 10 w / v%; preferably, the mass volume concentration of the unmodified or modified sodium hyaluronate solution is 5 to 8 w / v%.
[0022] As an implementation method, the volume concentration of the cross-linking agent is 0.01 to 2 v / v%; preferably, the volume concentration of the cross-linking agent is 0.1 to 0.5 v / v%.
[0023] As an implementable embodiment, the mass ratio of the silk fibroin nano-micron fiber suspension, the unmodified or modified sodium hyaluronate solution, and the cross-linking agent in step S2 is 25:12:12 to 2500:1200:12; preferably, the mass ratio of the silk fibroin nano-micron fiber suspension, the unmodified or modified sodium hyaluronate solution, and the cross-linking agent in step S2 is 25:12:12 to 2500:1200:12.
[0024] As an implementable embodiment, the condition for the cross-linking reaction in step S2 is: stirring in a 60° C. water bath for 2 to 24 hours; preferably, the condition for the cross-linking reaction in step S2 is: stirring in a 60° C. water bath for 4 to 8 hours.
[0025] As an implementation method, the non-polar solvent is one of paraffin solution, mineral oil, and vegetable oil; preferably, the non-polar solvent is soybean oil containing 1% (v / v) Span80; and the volume of the non-polar solvent added is greater than the volume of the silk fibroin nanoparticle suspension.
[0026] As an implementation method, the weak base in step S2 is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, calcium hydroxide, potassium hydroxide, potassium carbonate, and potassium bicarbonate. Preferably, the weak base is sodium hydroxide, and 10 g of sodium hydroxide is weighed, dissolved in water and fixed to 1 L, and the concentration is 1%.
[0027] As an implementation method, the cross-linking agent in step 2 is one or more of 1,4-butanediol diglycidyl ether, diglycidyl ether, 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether, bisphenol A diglycidyl ether derivative, resorcinol diglycidyl ether, 3,4-hydroxyphenylmethane triglycidyl ether and neopentyl glycol diglycidyl ether; preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether.
[0028] As an implementation method, the average particle size range of the silk fibroin fiber skeleton reinforced composite gel ball is 10μm to 10 mm, and the diameter of the silk fibroin nano-micron fiber in the skeleton material is 10 nm to 30μm; preferably, the average particle size range of the silk fibroin fiber skeleton reinforced composite gel ball is 100μm to 500μm, and the diameter of the silk fibroin nano-micron fiber in the skeleton material is 100nm to 10μm.
[0029] According to a third aspect of the present invention, there is provided an application of a silk fibroin fiber skeleton reinforced composite gel sphere, wherein the silk fibroin fiber skeleton reinforced composite gel sphere is used in a soft tissue filling injection.
[0030] As an implementation method, the soft tissue filling injection solution includes silk fibroin fiber skeleton reinforced composite gel balls and sodium hyaluronate solution, the concentration of the sodium hyaluronate solution is 0.1-2w / v%, and the volume ratio of the silk fibroin fiber skeleton reinforced composite gel balls to the sodium hyaluronate solution is (0.01-0.5g):1mL; preferably, the volume ratio of the silk fibroin fiber skeleton reinforced composite gel balls to the sodium hyaluronate solution is (0.05-0.3g):1mL.
[0031] According to a fourth aspect of the present invention, there is provided an application of a silk fibroin fiber skeleton reinforced composite gel sphere, wherein the silk fibroin fiber skeleton reinforced composite gel sphere is used in minimally invasive treatment or local tissue regeneration treatment.
[0032] As an implementation method, the silk fibroin fiber skeleton reinforced composite gel ball provided by the present invention can load cells, for example, stem cells, and can also load active substances, such as drugs, active factors, active polypeptides, etc.; the particle size of the silk fibroin fiber skeleton reinforced composite gel ball is controllable from 10μm to 10mm, and after loading cells, it can realize local injection therapy of loaded cell / active substance microspheres, thereby realizing minimally invasive treatment; in addition, the cells loaded by the silk fibroin fiber skeleton reinforced composite gel ball can better maintain cell survival rate, and can realize local release of drugs, thereby achieving local tissue regeneration and other treatments.
[0033] The advantages and beneficial effects of the present invention are:
[0034] (1) The present invention provides a silk fibroin fiber skeleton reinforced composite gel sphere formed by silk fibroin nano-micron fibers and sodium hyaluronate. Since the silk fibroin nano-micron fibers have a large number of functional groups on their surfaces, the silk fibroin nano-micron fibers can form gel microspheres through physical interactions such as hydrogen bonds, electrostatic effects and hydrophobic effects, and the nano-micron fibers and sodium hyaluronate can form gel microspheres through physical and chemical double crosslinking. The non-covalent bonds and covalent bonds between macromolecules can provide the silk fibroin fiber skeleton reinforced composite gel sphere with higher mechanical properties (cohesion), injectability, viscoelasticity and structural stability. For the silk fibroin fiber skeleton reinforced composite gel spheres with higher requirements for mechanical properties and degradation properties, this can also be achieved through multiple crosslinking of modified silk fibroin nanofibers.
[0035] (2) Since the physical and chemical properties of the two macromolecules of silk fibroin nano-micron fiber and sodium hyaluronate are quite different, the two phases cannot be uniformly compounded at the nanoscale due to the limitation of dissolution conditions. There has been no invention or research report on the construction of uniform silk fibroin nano-micron fiber / sodium hyaluronate nano-micron fiber reinforced composite gel spheres from the molecular or nanoscale. The present invention proposes for the first time a method for preparing a silk fibroin fiber skeleton reinforced composite gel sphere, comprising first preparing stable silk fibroin nano-micron fiber, dispersing it in a non-polar solvent under wetting conditions, and then continuing to add sodium hyaluronate solution to stir and disperse it uniformly, and there is a large amount of free hyaluronic acid between the wetted silk fibroin nanofibers. Sodium dispersion; under alkaline conditions, the functional groups in the main chain of sodium hyaluronate molecules (hydroxyl groups in primary alcohols) can covalently crosslink with the chemical groups in the crosslinker (for example, the epoxy groups at both ends of the molecule of 1,4-butanediol diglycidyl ether) (forming new chemical bonds, such as ether bonds). While sodium hyaluronate is crosslinked (matrix material), the surrounding silk fibroin nano-micron fibers can be "welded" and reinforced (skeleton material) to form silk fibroin fiber skeleton-reinforced composite gel balls, and the composition ratio, particle size, mechanical properties and degradability of silk fibroin nano-micron fibers and sodium hyaluronate can be finely controlled to achieve the synergy between material degradation rate and tissue regeneration rate.
[0036] (3) The silk fibroin fiber skeleton reinforced composite gel ball provided by the present invention has a protein / polysaccharide composition that mimics the composition of the human body, so the silk fibroin fiber skeleton reinforced composite gel ball has good biocompatibility and cell compatibility. The hyaluronic acid in the silk fibroin fiber skeleton reinforced composite gel ball can work synergistically. Hyaluronic acid has the functions of water retention, cartilage repair, and immune regulation. The introduction of silk fibroin nano-micron fiber material can improve the overall mechanical strength of the material and have a positive effect on the cell adhesion and cell growth promotion of the product. The superposition of the two has the advantage of 1+1>2 in tissue repair and filling. At the same time, the silk fibroin fiber skeleton reinforced composite gel ball can be used as a controlled release carrier of bioactive protein drugs (such as growth factors that induce tissue regeneration), nucleic acid drugs, and mRNA drugs for drug sustained release applications.
[0037] (4) The biosafety of the silk fibroin fiber skeleton reinforced composite gel sphere provided by the present invention can be guaranteed. The skeleton material is mainly composed of silk fibroin nano-micron fibers (>50 wt%). Compared with sodium hyaluronate cross-linked gel, the silk fibroin fiber skeleton reinforced composite gel sphere can greatly reduce the use of cross-linking agents (for example: 1,4-butanediol diglycidyl ether) while ensuring that the silk fibroin fiber skeleton reinforced composite gel sphere has an ideal tissue regeneration effect in clinical applications, thereby reducing the toxic side effects of cross-linking agent residues on the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a microscope image of the silk fibroin nano-micron fibers prepared in Example 1.
[0039] Figure 2 This is a microscope image of the silk fibroin fiber skeleton reinforced composite gel sphere prepared in Example 4.
[0040] Figure 3 This is a scanning electron microscope image of the silk fibroin fiber skeleton reinforced composite gel sphere prepared in Example 4.
[0041] Figure 4 This is a curve chart showing the change in pushing force of the silk fibroin fiber skeleton reinforced composite gel ball over time in Example 6.
[0042] Figure 5 This is a microscope picture of the silk fibroin fiber skeleton reinforced composite gel ball in Example 6 after high temperature wet heat sterilization. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with specific embodiments.
[0044] It should be noted that these embodiments are only used for the present invention, rather than limiting the present invention. Simple improvements to the method based on the concept of the present invention all fall within the scope of protection claimed by the present invention.
[0045] When preparing the silk fibroin fiber skeleton reinforced composite gel ball of the present invention, it is first necessary to prepare silk fibroin nano-micron fibers. The common methods for preparing silk fibroin nano-micron fibers in large quantities in the prior art include two methods: a "top-down" physical stripping method and a "bottom-up" regeneration spinning method. Among them, the "top-down" physical stripping method uses a denaturant to destroy the chemical bonds in the silk fiber molecular chain, and peels off layer by layer to obtain nano-micron fibers; the "bottom-up" regeneration spinning method is to dissolve the degummed silk first, and then re-assemble it into nano-micron fibers through "dry and wet" spinning. The implementation case of the present invention is to prepare silk fibroin nano-micron fibers by the "wet spinning" method, and silk fibroin nano-micron fibers prepared by other methods are also within the protection scope of the patent of the present invention.
[0046] The method for preparing the silk fibroin fiber skeleton reinforced composite gel sphere provided by the present invention comprises:
[0047] (1) An unmodified or modified silk fibroin solution is mixed with a denaturation inducer having a physical cross-linking effect, and the physical cross-linking between silk fibroin molecules is promoted by external stimulation through hydrogen bonding and hydrophobic interaction to form unmodified or modified silk fibroin nanometer and micrometer fibers, and then the denaturation inducer is removed by washing and centrifugation steps to obtain a silk fibroin nanometer and micrometer fiber suspension, wherein the external stimulation includes one or more of shear force, salt ions, temperature, pressure, and electric field force.
[0048] (2) dispersing the obtained unmodified or modified silk fibroin nanometer and micrometer fiber suspension in a non-polar solvent to form a mixed solution, and then adding the unmodified or modified sodium hyaluronate solution to the mixed solution, stirring evenly, and then adding a cross-linking agent to carry out a cross-linking reaction, using sodium hyaluronate to "weld" the silk fibroin nanometer and micrometer fibers into a composite gel ball suspension through chemical cross-linking, thereby obtaining a silk fibroin fiber skeleton reinforced composite gel ball suspension.
[0049] (3) Adding a cleaning agent to the suspension of the silk fibroin fiber skeleton reinforced composite gel spheres, removing excess non-polar solvents, surfactants, weak bases, uncross-linked sodium hyaluronate and cross-linking agents through washing and centrifugation operations, and obtaining silk fibroin fiber skeleton reinforced composite gel spheres; wherein the cleaning agent includes but is not limited to ethyl acetate, ethanol, deionized water, etc.; the silk fibroin fiber skeleton reinforced composite gel spheres not only have good flexibility, injectability and lubricity, but can also simulate the extracellular matrix environment (water retention and mechanical support) to the greatest extent, and the matrix content of each component can be flexibly adjusted, thereby controlling the cross-linking degree and thickness of the gel to achieve controllable degradation rate.
[0050] The mass volume concentration of the unmodified or modified silk fibroin solution is 5 to 40 w / v%; preferably, the mass volume concentration of the unmodified or modified silk fibroin solution is 15 to 25 w / v%.
[0051] The mass volume concentration of the unmodified or modified sodium hyaluronate solution is 0.1 to 10 w / v%; preferably, the mass volume concentration of the unmodified or modified sodium hyaluronate solution is 5 to 8 w / v%.
[0052] The volume concentration of the cross-linking agent is 0.01 to 2 v / v%; preferably, the volume concentration of the cross-linking agent is 0.1 to 0.5 v / v%.
[0053] Wherein, the cross-linking agent is one or more of 1,4-butanediol diglycidyl ether, diglycidyl ether, 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether, bisphenol A diglycidyl ether derivative, resorcinol diglycidyl ether, 3,4-hydroxyphenylmethane triglycidyl ether and neopentyl glycol diglycidyl ether. Preferably, the cross-linking agent is 1,4-butanediol diglycidyl ether.
[0054] The added volume of the non-polar solvent is greater than or equal to the volume of the substance before mixing.
[0055] The non-polar solvent is one of paraffin solution, mineral oil and vegetable oil; preferably, the non-polar solvent is soybean oil containing 1% (v / v) Span80.
[0056] Among them, a sodium hydroxide solution with a concentration range of 0.01 to 2% is first prepared, and then the solution is used to dissolve sodium hyaluronate. The pH of the sodium hyaluronate blend is 8 to 13, and the mass volume concentration of the sodium hyaluronate blend is 0.1 to 10 w / v%. Preferably, the pH of the sodium hyaluronate blend is 9.5, and the mass volume concentration of the sodium hyaluronate blend is 5 to 8 w / v%.
[0057] Among them, the mass ratio of silk fibroin nano-micron fiber suspension, unmodified or modified sodium hyaluronate solution, and cross-linking agent is 25:12:12-2500:1200:12; preferably, the mass ratio of silk fibroin nano-micron fiber suspension, unmodified or modified sodium hyaluronate solution, and cross-linking agent is 25:12:12-1000:500:12; more preferably, the mass ratio of silk fibroin nano-micron fiber suspension, unmodified or modified sodium hyaluronate solution, and cross-linking agent is 25:12:12.
[0058] The conditions for the cross-linking reaction in step (2) are: stirring in a 60° C. water bath for 2 to 24 hours; preferably, the conditions for the cross-linking reaction in step (2) are: stirring in a 60° C. water bath for 4 to 8 hours.
[0059] Among them, the average particle size range of the silk fibroin fiber skeleton reinforced composite gel sphere prepared by the preparation method is 10μm to 10 mm, and the diameter of the silk fibroin nano-micron fiber in the skeleton material is 10 nm to 30μm; preferably, the average particle size range of the silk fibroin fiber skeleton reinforced composite gel sphere is 100μm to 500μm, and the diameter of the silk fibroin nano-micron fiber in the skeleton material is 100nm to 10μm.
[0060] Application of silk fibroin fiber skeleton reinforced composite gel spheres prepared based on the preparation method in soft tissue filling injection.
[0061] Among them, the soft tissue filling injection solution includes silk fibroin fiber skeleton reinforced composite gel balls and sodium hyaluronate solution, the concentration of the sodium hyaluronate solution is 0.1-2w / v%, and the volume ratio of the mass of the silk fibroin fiber skeleton reinforced composite gel balls to the sodium hyaluronate solution is (0.01-0.5g):1mL; preferably, the volume ratio of the mass of the silk fibroin fiber skeleton reinforced composite gel balls to the sodium hyaluronate solution is (0.05-0.3g):1mL.
[0062] The silk fibroin fiber skeleton reinforced composite gel spheres prepared based on the preparation method can load cells, for example, stem cells, and can also load active substances, such as drugs, active factors, active peptides, etc.; the particle size of the silk fibroin fiber skeleton reinforced composite gel spheres can be controlled from 10 μm to 10 mm, and after loading cells, local injection therapy of loaded cell / active substance microspheres can be achieved, thereby achieving minimally invasive treatment; in addition, the cells loaded by the silk fibroin fiber skeleton reinforced composite gel spheres can better maintain cell survival rate, and local release of drugs can be achieved, thereby achieving treatments such as local tissue regeneration.
[0063] The present invention is further described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0064] Example 1
[0065] In this embodiment, a method for preparing silk fibroin nano-micron fibers is provided, comprising:
[0066] (1) Use a measuring cylinder to measure 1600 mL of polyethylene glycol with a molecular weight of 400 Da and mix it with 400 mL of deionized water to obtain an 80 v / v% polyethylene glycol solution.
[0067] (2) Weigh 100 g of unmodified or modified silk fibroin freeze-dried particles using an electronic balance, add 400 mL of deionized water to dissolve, and obtain a 25 w / v% unmodified or modified silk fibroin solution.
[0068] (3) Transfer 200 mL of polyethylene glycol solution to a 1000 mL beaker, add 50 mL of unmodified or modified silk fibroin solution to the beaker, and stir at 2500 rpm for 30 s.
[0069] (4) After adding 500 mL of deionized water to the mixed solution in (3), the mixed solution turns white. After washing and centrifugation to remove the polyethylene glycol, a silk fibroin nano-micron fiber suspension is obtained.
[0070] (5) Take a small amount of the silk fibroin nano-micron fiber suspension sample obtained in step (4), dry it and weigh it. The solid content of the silk fibroin nano-micron fiber suspension is measured to be 10.23%, and place it in a refrigerator at 4°C for later use.
[0071] Example 2
[0072] In this example, the fineness and length of the silk fibroin nano-micron fiber were analyzed. The specific steps were as follows: the silk fibroin nano-micron fiber suspension prepared in Example 1 was diluted to 1 mg / mL, 100 μL of the silk fibroin nano-micron fiber suspension was taken by a pipette and added to a glass slide, and covered with a cover glass, and the fineness and length of the sample were observed under a microscope (see the attached figure). Figure 1 As shown in the figure, the fineness and length of 100 silk fibroin nano-micron fibers were randomly measured in the field of view, and statistical analysis showed that the average fineness of the silk fibroin nano-micron fibers was 23.59 μm, and the average length was 289.84 μm.
[0073] Example 3
[0074] In this embodiment, a method for preparing a silk fibroin fiber skeleton reinforced composite gel ball is provided, comprising:
[0075] (1) Prepare a 1% Span80 soybean oil solution by adding 5 mL of Span80 to 500 mL of soybean oil and mixing thoroughly.
[0076] (2) Weigh 25 g of the silk fibroin nano-micron fiber suspension prepared in Example 1, disperse it in 505 ml of soybean oil containing 1% Span 80, and stir in a magnetic stirrer for 20 min to disperse the aggregated silk fibroin nano-micron fibers as evenly as possible in the oil phase.
[0077] (3) Add 20 g of 6% sodium hyaluronate solution prepared with 1% NaOH to (2) at a pH of 9.5, and stir in a magnetic water bath at 60°C for 20 minutes.
[0078] (4) Add 0.22% v / v 1,4-butanediol diglycidyl ether dropwise to the mixed solution stirred in (3); continue stirring in a 60° C. water bath for 4 h. The mass ratio of the silk fibroin nano-micron fiber suspension, the unmodified or modified sodium hyaluronate solution, and the cross-linking agent is 25:12:12 to 2500:1200:12. In this embodiment, the volume ratio of the silk fibroin nano-micron fiber suspension, the unmodified or modified sodium hyaluronate solution, and the cross-linking agent is 25:12:12.
[0079] (5) After standing for 30 min, the soybean oil was filtered out, and the soybean oil on the surface of the silk fibroin fiber skeleton reinforced composite gel sphere was further removed with oil-absorbing paper, and then washed with ethyl acetate. Finally, it was washed with anhydrous ethanol, 50% ethanol, and deionized water for three times respectively to obtain clean silk fibroin fiber skeleton reinforced composite gel sphere.
[0080] Microscope observation showed that when the volume ratio of silk fibroin nano-micron fiber suspension, unmodified or modified sodium hyaluronate solution, and cross-linking agent was 25:12:12, the resulting morphology of the silk fibroin fiber skeleton reinforced composite gel sphere was relatively good. The inner core of the silk fibroin fiber skeleton reinforced composite gel sphere was a porous network structure with silk fibroin nano-micron fibers as the skeleton, and the outer shell was wrapped with cross-linked sodium hyaluronate, which played a "welding" reinforcement role between the silk fibroin nano-micron fibers.
[0081] Example 4
[0082] In this embodiment, the particle size of the silk fibroin fiber skeleton reinforced composite gel sphere is statistically analyzed, and the specific steps are as follows: the silk fibroin fiber skeleton reinforced composite gel sphere suspension in Example 3 is diluted to 1 mg / mL, 100 μL of the suspension is taken by a pipette and added to a glass slide, and covered with a cover glass, and the morphology and particle size of the sample are observed under a microscope. It is found that sparse nano-micron-scale fibers are exposed around the silk fibroin fiber skeleton reinforced composite gel sphere, and the transparency gradually darkens from the outside to the inside. The outer surface is composed of transparent chemically cross-linked sodium hyaluronate (matrix material), and the darker interior is the skeleton formed by the aggregation of a large number of silk fibroin nano-micron fibers (such as the attached Figure 2As shown). The particle sizes of 100 silk fibroin fiber skeleton reinforced composite gel spheres were randomly measured in the microscopic observation field, and the average particle size of the silk fibroin fiber skeleton reinforced composite gel spheres was 125.56 μm after statistical analysis. In addition, the freeze-dried silk fibroin fiber skeleton reinforced composite gel sphere particles were observed by scanning electron microscopy, and it was clearly observed that the freeze-dried silk fibroin fiber skeleton reinforced composite gel sphere particles were composed of two parts: skeleton material (dispersed porous) and matrix material (continuous). The skeleton material was a continuous and interconnected porous form composed of silk fibroin nano-micron fibers (which can maintain the integrity of the structure), and the silk fibroin nano-micron fibers were chemically cross-linked and "welded" and wrapped by sodium hyaluronate (matrix material, which has collapse and poor rigidity) (as shown in the attached figure). Figure 3 as shown).
[0083] Example 5
[0084] In this embodiment, the porosity of the silk fibroin fiber skeleton reinforced composite gel ball is tested, and the specific steps are as follows: the pore size, bulk density and porosity of the freeze-dried silk fibroin fiber skeleton reinforced composite gel ball in Example 3 are tested using the AutoPore IV 9500 mercury intrusion instrument produced by Micromeritics, USA. The specific test principle is to use the characteristic that mercury does not infiltrate the surface of solid materials, and press mercury into the pores of the porous body with a certain pressure to overcome the resistance of the capillary, wherein a certain pressure value corresponds to a certain pore size value, and the corresponding mercury intrusion amount is equivalent to the pore volume corresponding to the pore size; this volume is the pore volume within the pore size range reflected by the two adjacent experimental pressure points before and after in the actual measurement; therefore, in the experiment, as long as the mercury intrusion amount of the porous material at each pressure point is measured, its pore size distribution and porosity can be obtained. It was found through testing (as shown in Table 1 below) that the core of the silk fibroin fiber skeleton reinforced composite gel ball has porous characteristics after freeze-drying, with an average pore size of 72.21μm and a porosity of more than 80%. The results confirmed that the silk fibroin nano-micron fibers were "welded" by sodium hyaluronate through chemical cross-linking to form silk fibroin fiber skeleton reinforced composite gel spheres, and after freeze-drying, the pores between the fibers in the inner core of the silk fibroin fiber skeleton reinforced composite gel sphere particles were larger.
[0085] Table 1 Mercury injection test data statistics
[0086] sample Average pore size (volume) Bulk density Porosity Example 3 72.21 μm 0.23 g / mL 80.83 %
[0087] Example 6
[0088] In this embodiment, the pushing force of the composite gel ball reinforced with a silk fibroin fiber skeleton is tested. The specific steps are as follows: the sample of Example 3 is tested for pushing force. An intelligent electronic tensile testing machine and a pressure measuring element with a pressure of 50N are used. A syringe with a 26G needle containing the composite gel ball reinforced with a silk fibroin fiber skeleton is vertically pressed at a speed of 30mm / min to make the composite gel ball reinforced with a silk fibroin fiber skeleton pass through the injection needle. The injection force changes over time. Figure 4 It can be seen that the silk fibroin fiber skeleton reinforced composite gel spheres with a solid content of 3.48wt% (dry weight / wet weight) can be directly and completely injected through a 26G needle, and the injection force of the whole process is between 20-25N, with an average injection force of 21.63N, and have good injectability.
[0089] Example 7
[0090] In this embodiment, the wet heat sterilization stability of the silk fibroin fiber skeleton reinforced composite gel spheres was tested, and the specific steps were as follows: (1) The silk fibroin fiber skeleton reinforced composite gel spheres in Example 3 were replaced with PBS, and the mixture was stirred and mixed to a solid content of 8 w / w% (silk fibroin fiber skeleton reinforced composite gel spheres 80 mg: PBS 1 g), and after vacuum defoaming treatment, the mixture was filled into a 1 mL syringe, and the syringe port was blocked with a rubber stopper; (2) The syringe in (1) was placed in a sterile sealed bag, and placed in a wet heat sterilization pot, and wet heat sterilized at 121°C for 20 minutes; (3) After the sterilization was completed, the syringe was taken out, a 26G injection needle was installed, and part of the sample was squeezed out into a test tube, PBS solution was added for suspension, 100 μL of the suspension was taken with a pipette and added to a glass slide, and covered with a cover glass, and the morphology and particle size of the sample were observed under a microscope. Figure 5 It can be seen that through observation, the particle size of the silk fibroin fiber skeleton reinforced composite gel spheres tended to increase after moist heat sterilization, and some fibers were exposed on the surface. This may be related to the degradation of partially cross-linked sodium hyaluronate under high temperature conditions, affecting the structural integrity of a small number of silk fibroin fiber skeleton reinforced composite gel spheres.
[0091] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A silk fibroin fiber skeleton reinforced composite gel ball, characterized in that: The silk fibroin fiber skeleton reinforced composite gel ball consists of two parts: a skeleton material and a matrix material. The skeleton material consists of unmodified or modified silk fibroin nano-micron fibers, and the matrix material consists of chemically cross-linked unmodified or modified sodium hyaluronate. The average particle size range of the silk fibroin fiber skeleton reinforced composite gel ball is 10 μm to 10 mm. The content of the silk fibroin nano-micron fibers in the silk fibroin fiber skeleton reinforced composite gel ball is greater than the content of sodium hyaluronate. The diameter of the silk fibroin nano-micron fibers in the skeleton material is 10 nm to 30 μm.
2. The silk fibroin fiber skeleton reinforced composite gel ball according to claim 1, characterized in that: The silk fibroin nano-micron fiber is composed of unmodified silk fibroin or modified silk fibroin, wherein the modified silk fibroin is obtained by modifying the unmodified silk fibroin with a first type of functional group, wherein the first type of functional group includes one or more of alkyl, amino, carboxyl, sulfonic acid, thiol, epoxy, azo, imidazole, pyrimidine, maleimide, biotin, bindin, and fluorescent groups, and the molecular weight of the unmodified or modified silk fibroin ranges from 1 to 500 kDa; the modified sodium hyaluronate is obtained by modifying the unmodified sodium hyaluronate with a second type of functional group, wherein the second type of functional group includes one or more of alkyl, acyl, amino, aldehyde, cyano, hydrazide, thiol, imidazole, pyrimidine, biotin, bindin, and fluorescent groups.
3. The silk fibroin fiber skeleton reinforced composite gel ball according to claim 2, characterized in that: The modified silk fibroin is covalently cross-linked silk fibroin, which is obtained by reacting a compound with hydroxyl groups and amino groups in the silk fibroin molecules. The modified sodium hyaluronate is covalently cross-linked modified sodium hyaluronate, which is obtained by reacting a compound with hydroxyl groups in the sodium hyaluronate molecular chain. The compound is one or more of acrylic anhydride, acryloyl chloride, methacrylic anhydride, methacryloyl chloride, ethylacrylic anhydride, ethylacryloyl chloride, hydroxyacrylic anhydride, and hydroxyacryloyl chloride.
4. The silk fibroin fiber skeleton reinforced composite gel ball according to claim 1, characterized in that: The chemical crosslinking crosslinking agent is one or more of 1,4-butanediol diglycidyl ether, diglycidyl ether, 1,3-diglycidyl ether glycerol, bisphenol A diglycidyl ether, bisphenol A diglycidyl ether derivatives, resorcinol diglycidyl ether, 3,4-hydroxyphenylmethane triglycidyl ether and neopentyl glycol diglycidyl ether.
5. The silk fibroin fiber skeleton reinforced composite gel ball according to claim 1, characterized in that: The average particle size of the silk fibroin fiber skeleton reinforced composite gel ball is in the range of 100 μm to 500 μm, and the diameter of the silk fibroin nano-micron fiber in the skeleton material is in the range of 100 nm to 10 μm.
6. A method for preparing a silk fibroin fiber skeleton reinforced composite gel ball according to any one of claims 1 to 5, characterized in that: include: Step S1: mixing an unmodified or modified silk fibroin solution with a denaturation inducing agent solution having a physical cross-linking effect, promoting physical cross-linking between silk fibroin molecules through hydrogen bonds and hydrophobic effects through external stimulation to form unmodified or modified silk fibroin nanometer and micrometer fibers, and obtaining an unmodified or modified silk fibroin nanometer and micrometer fiber suspension after washing and centrifugation; wherein the external stimulation includes one or more of shear force, salt ions, temperature, pressure, and electric field force; Step S2: dispersing the obtained unmodified or modified silk fibroin nano-micron fiber suspension in a non-polar solvent to form a blended solution, adding the unmodified or modified sodium hyaluronate solution to the blended solution, stirring evenly, and then adding a cross-linking agent to perform a cross-linking reaction to obtain a silk fibroin fiber skeleton reinforced composite gel ball suspension; Step S3: adding a cleaning agent to the suspension of the silk fibroin fiber skeleton reinforced composite gel spheres, washing and centrifuging to obtain the silk fibroin fiber skeleton reinforced composite gel spheres.
7. The method for preparing a silk fibroin fiber skeleton reinforced composite gel ball according to claim 6, characterized in that: The denaturation inducing agent solution having a physical cross-linking effect is one or more of methanol, ethanol, isopropanol, acetone, 2-phenylethanol, phenoxyethanol, and polyethylene glycol. After the unmodified or modified silk fibroin solution is mixed with the polyethylene glycol solution, it is stirred at a speed of 2500 rpm for 30 seconds, and after washing and centrifugation, a silk fibroin nano-micron fiber with uniform thickness and length is obtained, and then step S1 is performed; the molecular weight range of polyethylene glycol in the polyethylene glycol solution is 200 to 20000 Da, the mass volume concentration of the polyethylene glycol solution is 50 to 100 w / v%, and the mass volume concentration of the unmodified or modified silk fibroin solution is 5 to 40 w / v%.
8. The method for preparing a silk fibroin fiber skeleton reinforced composite gel ball according to claim 6, characterized in that: In the step S2, the unmodified or modified sodium hyaluronate solution is compounded with an alkaline solution, the pH of the alkaline solution is 8-13, the mass volume concentration of the unmodified or modified sodium hyaluronate solution is 0.1-10w / v%, the volume concentration of the cross-linking agent is 0.01-2v / v%, and the mass ratio of the silk fibroin nano-micron fiber suspension, the unmodified or modified sodium hyaluronate solution, and the cross-linking agent in the step S2 is 25:12:12-2500:1200:12; the conditions for the cross-linking reaction in the step S2 are: stirring in a 60°C water bath for 2-24h, and the non-polar solvent is one of paraffin solution, mineral oil, and vegetable oil.
9. An application of the silk fibroin fiber skeleton reinforced composite gel sphere according to any one of claims 1 to 5, for use in a soft tissue filling injection, the soft tissue filling injection comprising the silk fibroin fiber skeleton reinforced composite gel sphere and a sodium hyaluronate solution, the concentration of the sodium hyaluronate solution being 0.1 to 2 w / v%, and the volume ratio of the mass of the silk fibroin fiber skeleton reinforced composite gel sphere to the sodium hyaluronate solution being (0.01 to 0.5 g): 1 mL.
10. Use of the silk fibroin fiber skeleton reinforced composite gel sphere according to any one of claims 1 to 5 in minimally invasive treatment or local tissue regeneration treatment.
Citation Information
Patent Citations
Fibroin porous microsphere with nano-fiber microstructure and preparation method thereof
CN108553689A
Long-acting sustained-release cell scaffold, and preparation method and application thereof
CN109602952A
Nanofiber structures and methods of use thereof
CN110099679A
Composite gel ball based on physical and chemical crosslinking core-shell structure and preparation method of composite gel ball
CN115073924A
Structural protein / hyaluronic acid composite micro-nano particle, particle hydrogel material and application
CN115521627A